Gas tragedy, an eye witness - Prajapati, H. L., 1947- (New Delhi : Mittal Publications, 2003)
An eyewitness account of the Bhopal Union Carbide Plant Disaster, Bhopal, India, 1984
Includes index
Keywords: Bhopal Union Carbide Plant Disaster, Bhopal, India, 1984; Pesticides industry -- Accidents -- India -- Bhopal